Membrane bound Indian clade C HIV-1 envelope antigen induces antibodies to diverse and conserved epitopes upon DNA prime/protein boost in rabbits. Issue 21 (5th May 2016) - Rangasamy, Sneha Priya; Menon, Veena; Dhopeshwarkar, Priyanka; Pal, Ranajit; Vaniambadi, Kalyanaraman S.; Mahalingam, Sundarasamy
Highlights: Effect of DNA prime on antibody induction by Indian clade C gp145 trimer immunogen. DNA encoding gp145 with transmembrane exposed quaternary epitopes the best. Membrane bound gp145 DNA prime induced broader range of epitopes than soluble gp145. Neutralization titers were lower in DNA prime-protein boost than protein only. Abstract: The partial success of RV144 human clinical trial demonstrated that ALVAC prime/envelope protein boost vaccine regimen may represent a promising strategy for the development of an effective HIV-1 vaccine. Our earlier study demonstrated that a trimeric HIV-1 envelope gp145 from an Indian clade C isolate elicited cross clade neutralizing antibodies primarily towards Tier 1 isolates. In the present study, we examined the immunogenicity of DNA prime/envelope protein boost vaccine in rabbits using gp160 DNA of the Indian clade C isolate with various cytoplasmic tail truncations and trimeric gp145 protein. Cytoplasmic tail mutants of gp160 exposed epitopes that reacted strongly with a number of broadly neutralizing human monoclonal antibodies against HIV-1. Overall, envelope specific titers were found to be similar in all rabbit groups with higher pseudovirus neutralization in protein only immunized rabbits. The complete linear epitope mapping of rabbit immune sera revealed strong binding to C1, C2, V3, C3 and C4 domains of gp145. Importantly, reactivity of gp41 ecto-domain peptides was observed in DNA prime/protein boost sera but not in the sera of rabbits immunized with protein alone. Moreover, membrane anchored but not soluble envelope encoding DNA immunization elicited antibodies against linear epitopes on the conserved gp41 ecto-domain. Together, these results suggest that priming with DNA encoding cytoplasmic domains of Env alters the quality of antibodies elicited following protein boost and hence may be utilized to generate protective immunity by HIV-1 vaccine.